Combining EGFR-TKI With SAHA Overcomes EGFR-TKI-Acquired Resistance by Reducing the Protective Autophagy in Non-Small Cell Lung Cancer - Cao, Peijun; Li, Yongwen; Shi, Ruifeng; Yuan, Yin; Gong, Hao; Zhu, Guangsheng; Zhang, Zihe; Chen, Chen; Zhang, Hongbing; Liu, Minghui; Pan, Zhenhua; Liu, Hongyu; et al. (Frontiers in Chemistry, 2022)
At present, lung cancer is the cancer with the highest mortality rate in the world. The emergence of EGFR tyrosine kinase inhibitors (TKIs) has greatly improved the survival of non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR)-TKI sensitive mutations.Unfortunately, drug resistance is the outcome of most patients. In our research, we found that EGFR tyrosine kinase inhibitors ( both gefitinib and osimertinib ) can induce autophagy in non-small- cell lung cancer (NSCLC) cell lines. Compared with parental sensitive cells, drug-resistant cells have higher autophagy activity. The use of autophagy inhibitor could enhance the toxicity of gefitinib and osimertinib,which indicates that the enhancement of protective autophagy might be one of the mechanisms of EGFR TKI resistance in non-small- cell lung cancer (NSCLC). In addition, we found that increased autophagy activity is associated with decreased EZH2 expression. Knockdown of EZH2 or EZH2 inhibitor treatment could lead to the increasing of autophagy in NSCLC cells, indicating that EZH2 is a negative regulator of autophagy. We revealed that the increasing of autophagy caused by the reduction of EZH2 was reversed in vitro and vivo ,when combinating gefitinib or osimertinib with SAHA, a broad-spectrum Histone Deacetylase inhibitor (HDACi), In conclusion,our results indicated that the combination of EGFR-TKIs and SAHA may be a new strategy to overcome EGFR TKIs acquired resistance.